Le processus de patrimonialisation d’un petit fromage de montagne, le persillé de Tarentaise - Christiane Dunoyer (In Situ)
The Tarentaise is a long alpine valley located in the department of Savoie. It is a land of contrasts, with a wide variety of landscapes and micro-terroirs, specific localities with specific products, but also many different sociological realities. Agricultural zones coexist with the largest skiing domains in the world. In the upper part of the valley, some goat farmers have organised their production around a local blue veined cheese, the persillé, of which they claim to have inherited the manufacturing processes from their parents and grandparents. Information collected during an anthropological study on culinary and food practices in the Tarentaise, commissioned by the Musée savoisien (Chambéry) between January 2018 and January 2019, make it possible here to give an account of the context in which this cheese evolved. After a certain decline, when the persillé was overshadowed by the prestigious Beaufort cheese, its new success was founded on the appeal that non-industrial local products exercises over consumers today. The article aims to illustrate the issues surrounding the revival of this cheese. It describes and analyses the variety of cheese products bearing the same name (on the diachronic level as well as on a synchronic one) and looks at the tensions between the different producers, each one claiming a special status within the triad formed by the producer, the persillé and the territory.